Female preference for super-sized male ornaments and its implications for the evolution of ornament allometry - Thomas C. Summers; Terry J. Ord (Evolutionary Ecology, 2022)
It has been argued that disproportionately larger ornaments in bigger males—positive allometry—is the outcome of sexual selection operating on the size of condition dependent traits. We reviewed the literature and found a general lack of empirical testing of the assumed link between female preferences for large ornaments and a pattern of positive allometry in male ornamentation. We subsequently conducted a manipulative experiment by leveraging the unusual terrestrial fish, Alticus sp. cf. simplicirrus , on the island of Rarotonga. Males in this species present a prominent head crest to females during courtship, and the size of this head crest in the genus more broadly exhibits the classic pattern of positive allometry. We created realistic male models standardized in body size but differing in head crest size based on the most extreme allometric scaling recorded for the genus. This included a crest size well outside the observed range for the study population (super-sized). The stimuli were presented to free-living females in a manner that mimicked the spatial distribution of courting males. Females directed greater attention to the male stimulus that exhibited the super-sized crest, with little difference in attention direct to other size treatments. These data appear to be the only experimental evidence from the wild of a female preference function that has been implicitly assumed to drive selection that results in the evolution of positive allometry in male ornamentation.